The Structured Innovation System: Optimizing Patent Filing and Obtaining Global Protection - Raymond R. Tjandrawinata; Henry Soelistyo Budi; Ina Heliany (Journal of Social Science, 2025)
Innovation is a fundamental driver of economic growth and technological advancement, yet securing intellectual property rights remains a complex challenge. The structured approach to innovation emphasizes key pathways for patent filing and global protection, ensuring a streamlined transition from ideation to commercialization. Drawing from Structured Innovation framework and other theoretical perspectives, this study examines how systematic innovation processes, strategic decision-making, and collaborative ecosystems contribute to robust intellectual property strategies. Through a comparative analysis of legal frameworks, case studies, and empirical data, this study presents insights for inventors and organizations seeking to optimize their patent portfolios. The findings underscore the importance of integrating structured methodologies with legal foresight to enhance global competitiveness and innovation sustainability. Future research directions include the application of structured patent filing to emerging fields such as AI-driven biotechnology and blockchain-based intellectual property management.